Analisis Kepemimpinan Kepala Sekolah di Sekolah Dasar Kecamatan Sijamapolang, Kabupaten Humbang Hasundutan - Daniaty Daniaty; Popy Sigalingging; Wildansyah Lubis; Winara Winara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the leadership of elementary school principals in Sijamapolang District, Humbang Hasundutan Regency, using a qualitative approach with a case study method. The research focuses on how school principals carry out their leadership roles in managerial functions, academic supervision, and fostering social relationships within the school environment. Data were collected through in-depth interviews, direct observations, and document analysis involving three purposively selected elementary schools as case study subjects. The findings indicate that school principals play a strategic role in creating a conducive school climate, motivating teachers, and encouraging the participation of school stakeholders. However, challenges such as limited resources, low community involvement, and a lack of leadership training were found to affect leadership effectiveness. These findings provide valuable insights for developing school leadership capacity in remote areas and emphasize the importance of ongoing professional development to improve the quality of education.